Polyolefin chain shuttling at ansa-metallocene catalysts: legend and reality. (5th May 2021) - Cannavacciuolo, Felicia Daniela; Vittoria, Antonio; Ehm, Christian; Cipullo, Roberta; Busico, Vincenzo
Graphical abstract: Highlights: The propensity of metallocenes to mediate propene CCTP was explored through HTE tools. The rac -Me2 Si(2-Me-4-Ph-1-Ind)2 ZrCl2 catalyst does not yield stereoblock PP materials. Method to unambiguously demonstrate the occurrence of CCTP in isotactic propene polymerization. Abstract: Several papers have claimed the amenability for binary metallocene systems to undergo coordinative chain transfer polymerization (CCTP) to produce stereoblock isotactic/syndiotactic polypropylene materials. In this work, we explored through high throughput experimentation (HTE) tools and methods the propensity of the isotactic-selective rac -Me2 Si(2-Me-4-Ph-1-Ind)2 ZrCl2 (2 ) catalyst to mediate propene CCTP, individually or in tandem with the syndiotactic-selective ansa -zirconocene Ph2 C(Cp)(2, 7-di- t Bu-9-Flu)ZrCl2 (3 ), using ZnEt2 and methylalumoxane (MAO) as chain shuttling agents. The results demonstrated that 2 is not prone to propene CCTP, and therefore does not yield stereoblock PP materials when used in racemic form or in tandem with other metallocenes. An unambiguous method to demonstrate the occurrence of CCTP in isotactic propene polymerization, based on the microstructural characterization of the sample by 13 CNMR spectroscopy, is also proposed.